Parking, travel behavior, and working from home - Hao Ding; Michael Manville (Journal of Transport and Land Use)
We examine parking policy’s potential to influence people’s travel behavior, including their decision to work from home. Drawing on the California Household Travel Survey, we first show that most households have residential parking included in the rent or purchase price of their home, that most employed individuals have free parking at work, and most vehicle trips end with a free parking space, usually off-street. Furthermore, we confirm that most cars are mostly parked; the median household vehicle in California spends 23 hours a day parked. Using regression models, we uncover strong associations between choosing to drive and having free parking at work or home. We find that households with bundled parking are more likely to drive, and less likely to use transit. We further find that employees with free parking at work are more likely to drive for their commutes. Finally, we estimate regressions that analyze the decision to work from home. Data constraints make these regressions less conclusive, but our results suggest, consistent with previous literature, that working from home is associated with more, rather than less, vehicle travel.